Subjective and Objective Outcomes in Patients With COPD After Pulmonary Rehabilitation – The Impact of Comorbidities - Charikiopoulou, Maria; Nikolaidis, Pantelis Theodoros; Knechtle, Beat; Rosemann, Thomas; Rapti, Aggeliki; Trakada, Georgia (Frontiers in Physiology, 2019)
Background: Chronic obstructive pulmonary disease (COPD) is a heterogeneous disease with multiple systemic manifestations and comorbidities, which contribute independently to its total morbidity and mortality. Pulmonary rehabilitation is an evidence-based intervention that is indicated for COPD patients who remain symptomatic, despite optimal pharmacological therapy. Although it is well documented in pure COPD, the role of pulmonary rehabilitation is uncertain in coexisting comorbidities. The aim of the present study was to clarify the effect of a pulmonary rehabilitation program in COPD patients with concomitant comorbidities. Methods: Thirty two patients with COPD were evaluated before and after a comprehensive pulmonary rehabilitation program, in terms of dyspnea, quality of life (QOL), pulmonary function tests and exercise capacity. The patients were also divided into two groups, according to the presence or the absence of comorbidities. Patients with none or only one comorbidity (Group 1, n=11) were compared to those who had two or more comorbidities (Group 2, n=21). Results: All patients significantly improved in dyspnea, as expressed by modified Medical Research Council scale and the COPD assessment Test (p<0.001), QOL as assessed by the St George respiratory questionnaire (p<0.001) and exercise tolerance in six minute walking test (p<0.001). Peak oxygen uptake relatively increased and body mass decreased in Group 1 compared to Group 2 (p<0.05). Conclusions: Pulmonary rehabilitation in COPD seems to be beneficial for all patients, independently of the presence, the number or the nature of their comorbidities. Thus, the presence of comorbidities must not represent an exclusion criterion for patients that are referred to pulmonary rehabilitation programs.